Factors at first diagnosis of tuberculosis associated with compliance with the Directly Observed Therapy (DOT) in the Limpopo Province, South Africa - K. Peltzer; H. Onya; P. Seoka; F.M. Tladi (AOSIS, 2002)
The aim of this study is to compare and contrast health beliefs, demographic and socio-economic variables, causative beliefs, knowledge, health-seeking behaviour and health provider-patient interaction of compliant and non-compliant tuberculosis patients. The sample included 219 consecutive new sputum-smear and/or culture positive pulmonary tuberculosis patients registered between October 1999 and March 2000 in three hospitals in the Limpopo Province of South Africa. The patients were 144 (65.8%) men and 75 (34.2%) women in the age range of 18 to 79 years (M age 35.9 yr., SD= 12.6). The consultation at first diagnosis was observed and tape-recorded. Thereafter an interview was conducted and a questionnaire was face-to-face administered with the patient including knowledge, causative beliefs, health seeking, and Health Belief Model items. Discriminant analysis between compliant and non-compliant groups after six months follow-up showed that the quality of the health practitioner-patient interaction and causative belief were associated with compliance behaviour whereas knowledge, onset of TB, sociodemographic variables, health care seeking, and health beliefs were not associated.